IN-SERVICE TEACHERS’ PROBLEMS IN DEVELOPING ENGLISH TEXTBOOKS FOR ELEMENTARY SCHOOL STUDENTS - Fatimah, Nur; Sarage, Japen (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2024)
In-service teachers are required to fulfill responsibilities for administrative and non-administrative stuffs. However, there are some teachers who developed English materials in the form of textbooks for young learners. These teachers were involved in this study on developing English materials for elementary school students. This research is aimed at revealing the in-service teachers’ problems in developing the materials into English textbooks for young learners and their solutions. This research involved seven in-service teacher authors developing English textbooks in some private elementary schools in Yogyakarta city. It applied qualitative research method. The data collection technique used a questionnaire containing open-ended questions. It revealed the data on the teachers’ profiles, the teachers’ problems in developing English textbooks and their solutions. The data were put into categories to help achieve the research objectives. From the study, it was found out that the problems in developing English materials are related to the material selection, language points suitable for young learners, presentation of the materials. The research subjects set these strategies to solve the problems faced during the materials development by sharing and discussion, supervision, finding other existing resources, and creating their own materials. The finding highlights that examples of materials and various forms of material presentation need to be exposed to teacher authors as well as to pre-service teachers and other textbook authors to help them develop better teaching materials.